Evaluating Invariances in Document Layout Functions - Macdonald, Alexander J.; Brailsford, David F.; Lumley, John (ACM Press, 2006)
With the development of variable-data-driven digital presses - where each document printed is potentially unique - there is a need for pre-press optimization to identify material that is invariant from document to document. In this way rasterisation can be confined solely to those areas which change between successive documents thereby alleviating a potential performance bottleneck. Given a template document specified in terms of layout functions, where actual data is bound at the last possible moment before printing, we look at deriving and exploiting the invariant properties of layout functions from their formal specifications. We propose future work on generic extraction of invariance from such properties for certain classes of layout functions.